The Two-Legged Strategy; How Batu City Farmers Rationally Navigate the Tourism Industry - Sofiurrohman; Chawa, Anif Fatma; Nurhadi, Iwan; Putra, Moch Hisyam (EcceS: Economics, Social, and Development Studies, 2025)
This study explores how farmers in Bulukerto Village, Batu City, rationally diversify their livelihoods amid an agricultural crisis and expanding tourism. It addresses three core questions; (1) how farmers respond to agrarian decline through diversification, (2) how unequal access, social capital, and agrarian identity influence their decisions, and (3) how theoretical synthesis explains this dynamic within structural constraints. The research combines James S. Coleman’s Rational Choice Theory, which highlights decisions based on material and non-material resources, cost-benefit logic, values, and social norms, with Henry Bernstein’s political economy approach, which emphasizes power structures, asset control, and class relations. To bridge these perspectives, the study also draws on the concepts of bounded rationality and embedded agency. A qualitative case study approach was used, focusing on farmers in Bulukerto Village, Bumiaji Subdistrict, Batu City. Data collection techniques included semi-structured interviews, non-participant observation, and document review. Thematic analysis identifies three diversification types: (1) capital-based, involving formal tourism ventures by farmers with financial or institutional access; (2) labor-based, such as driving or guiding, pursued by low-capital farmers through informal networks; and (3) informal household-scale strategies led by women or youth, often using digital platforms. This study concludes that sustainable rural diversification requires equitable access to productive resources, digital upskilling, and inclusive tourism programs that preserve agrarian identity. It offers a multi-level analytical lens that integrates agency, social structure, and local context in understanding livelihood transitions in post-agrarian rural areas. Policy recommendations call for transparent resource allocation in tourism, empowering farmer cooperatives for fair benefit-sharing, and promoting agritourism that balances traditional land use with new income streams.